Do bullying ao cyberbullying: história e memórias escolares (1993-2011) - Santos, Silvânia da Silva (2015)
The present study, From bullying to cyberbullying: history and memories (1993-2011), (Do bullying ao cyberbullying: história e memórias escolares), is a proposal of investigation that contemplates the history of school events in the present time. In this context, the study recreates facts and events of our time and representations of lived and imagined moments as a manner of building history. The investigation uses Oral History methodology, utilizing living participants‟ memories, and potential deponents, open to collaboration. The study presents three main goals. It aims to revel the construction process of the object of study; to show the dialogues among the studies of Halbwachs (2006), Ricoeur (2012), Bosi (1994), Le Goff (2013), Thompson (1992), Meihy (2007), and others; about history, memory, present time and oral history; and to show the articulation among Olweus (1993), Silva (2010), Lima (2011), Calhau (2011), Fante (2012), etc.; that see bullying and cyberbullying as anactual “problematic” poorly studied. Because of the constant changes in history throughout the time, future generations will be able to “dive” in memories of the past, preserving them alive and building connections for its comprehension and reconstruction.